Job displacement penalties in Japan - Michael Bognanno; Lisa Delgado (Institute for the Study of Labor (IZA), 2005)
The costs of job displacement are examined on a sample of Japanese workers successfully provided job placement services from 2000 to 2003, a period of economic stagnation and structural change in Japan. We find that displaced workers suffer a loss of approximately 1,100 for each additional year of age. Workers also incur a large penalty when they change industries after being displaced. The age-earnings loss relationship is consistent with the operation of a delayed compensation scheme in large firms.
Keywords: J31; J41; J63; J65; 330; job displacement cost; Japan